GAMBARAN KADAR VITAMIN D PADA PENGGUNAAN OBAT ANTI EPILEPSI TUNGGAL GENERASI PERTAMA - Sri Utami Ningsih, Fitri Octaviana, Lyna Soertidewi, Astri Budikayanti, Joedo Prihartono (Neurona Majalah Kedokteran Neuro Sains, 2013)
INTRODUCTION ANTIEPILEPTIC DRUGS AEDS ARE KNOWN TO INTERFERE VITAMIN D METABOLISM THROUGH ACTIVATING OF THE PREGNANE X RECEPTOR PXR THIS PXR INCREASED REGULATION 24HYDROXYLASEAND TRIGGER VITAMIN D CHANGES INTO INACTIVE METABOLITES AS FOUND IN LEBANON HYPOVITAMINOSIS D REACHES 70 AND 236 IN THAILAND CARBAMAZEPINE PHENYTOIN PHENOBARBITAL AND VALPROIC ACID THE FIRST GENERATIONAEDS ARE WIDELY USED IN CIPTO MANGUNKUSUMO HOSPITAL KNOWLEDGE OF VITAMIN D LEVEL PREVALENCE OF HYPOVITAMINOSIS D AND ITS INFLUENCING FACTORS CAN BE REDUCED THE ADVERSE EFFECT OF LONGTERM AEDS